Chemoselective photocatalytic oxidation of alcohols to aldehydes and ketones by nitromethane on titanium dioxide under violet 400 nm LED light irradiation. Issue 12 (11th March 2020) - Rahimi Niaraki, Azam; Saraee, Mohammad Reza; Kazemi, Foad; Kaboudin, Babak
Abstract : In this study, for the first time, nitroalkanes, especially nitromethane, have been used as electron acceptors for the highly chemoselective oxidation of alcohols in the presence of a TiO2 photocatalyst under 400 nm LED irradiation. Abstract : In this study, for the first time, nitroalkanes, especially nitromethane, have been used as electron acceptors for the highly chemoselective oxidation of alcohols in the presence of a TiO2 photocatalyst under 400 nm LED irradiation. The reactions showed excellent selectivity for the production of aldehydes. Interestingly, aldehydes such as benzaldehyde and p -methoxybenzaldehyde are stable under the reaction conditions. In the case of the use of 2-nitropropane and 2-methyl-2-nitropropane, the product imine, which is the result of the reaction of the aldehyde with aliphatic amine, is also obtained.